Optimization of ovum pick-up-in vitro fertilization and in vitro growth of immature oocytes in ruminants - Kenichiro SAKAGUCHI (The Journal of Reproduction and Development)
Due to the strong demand for embryo production from young and genotyped superior animals using ovum-pick up (OPU) combined with in vitro fertilization (IVF), the number of in vitro-produced embryos has exceeded that of in vivo-derived embryos globally since 2016. One of the merits of OPU-IVF is that the administration of follicle-stimulating hormone (FSH) is not essential, while FSH treatment prior to OPU promotes oocyte developmental competence. Thus, investigations are needed to optimize OPU-IVF protocols with and without FSH. In addition, OPU enables oocyte collection from antral follicles in living animals. However, there are numerous immature oocytes in follicles at earlier stages, which are potentially destined to degenerate in ovaries. The technology used to foster acquisition of maturational and developmental competences in these immature oocytes is called in vitro growth (IVG). IVG is expected to contribute to assisted reproductive technologies for livestock, humans, and endangered species. However, no offspring from preantral follicles has been reported using IVG in animals other than in mice. Furthermore, IVG can be used to investigate factors affecting the fertility and developmental competence of oocytes by reconstituting follicle growth at each stage in vitro, which cannot be evaluated in vivo. Here, the technological progress of the optimization of immature bovine oocyte utilization is reviewed alongside findings from a variety of other ruminants.